Back Cover: Bacterial Growth and Adaptation in Microdroplet Chemostats (Angew. Chem. Int. Ed. 34/2013). Issue 34 (15th July 2013) - Jakiela, Slawomir; Kaminski, Tomasz S.; Cybulski, Olgierd; Weibel, Douglas B.; Garstecki, Piotr
<x xml:space="preserve">Abstract</x> High‐throughput evolutionary studies are now possible with the technology introduced by P. Garstecki et al. in their Communication on page 8908 ff.. They demonstrate a microfluidic device for manipulating and monitoring hundreds of bacterial populations at the same time. They also study bacterial adaptation to changing chemical environments and track the evolution of antibiotic resistance.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>